Psychological empowerment for cognitive demand tasks / Siti Aleisha Mohamad Benyamin - Mohamad Benyamin, Siti Aleisha (2020)
Technology should help workers in assisting with the changes that comes with greater risks, and higher demands on the intellectual capacities of employees. The employees are expected to be updated and aware of the demand needs, to improve their work performance. and stay relevant to the industries' rapid changes. This pose a significant amount of cognitive demands. Unfortunately, the employees cannot simply ditch their work when they are facing with cognitive demand tasks. They need rnotivations, some sort of psychological empowerment to help them cope with the demands. In order to be motivated, the employees are required to have intrinsic motivation and locus control on themselves. Psychological empowerment is known to play a crucial role in developing the effectiveness of both organizations and individuals.Besides, empowerment is suggested to give significant effects on the work performance of an employee, and innovation performance. With high cognitive demands at the workplace, psychological empowerment can ease the mental strain of an employee in tackling the issue, besides improving their competency and innovation performance. This study aims at investigating the impact of psychological empowerment's mechanisms in tackling cognitive demand tasks to boost the work performance among construction professionals.